Foreign exchange regulatory framework and characteristics of the Argentine exchange market regarding the transfer of funds from and to foreign countries - Miguel Angel Pesce (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2011)
The purpose of this document is to prove that the establishment in Argentina of regulations and records for exchange market transactions has a positive externality with respect to the prevention and control of asset laundering and potential terrorist financing, thus making this type of criminal transactions through this channel extremely difficult.
Keywords: F31; G18; K14; 330; Argentina; exchange rate market regulations; asset laundering; terrorist financing; Devisenmarkt; Wechselkurspolitik; Argentinien